Optimal dispatch of combined heat and power plant in integrated energy system: A state of the art review and case study of Copenhagen. (February 2019) - Wang, Jiawei; You, Shi; Zong, Yi; Træholt, Chresten; Zhou, You; Mu, Shujun
Abstract: This paper presents and classifies a state of the art optimal dispatch review of combined heat and power plants (CHP) in integrated energy systems. Comparing the purposes of increasing renewable energy integration and profits of CHP operation, two groups of literatures, cost and market based optimal dispatch of CHP plants are studied. The flexibility in terms of reducing wind power curtailment and increasing revenue by providing ancillary service is discussed. A case study of optimal dispatch of a CHP plant under the heat market in Copenhagen, Denmark is proposed, where the flexibility is compared with different CHP unit types, operation modes and heat accumulators' integration.